Nilai-Nilai Pendidikan Karakter Islami dalam Perspektif Kitab Al-Arbain An-Nawawiyyah Karya Syaikh An-Nawawi - Nur Dina Agustianti; Nurul Mubin; Ngatoillah Linnaja (Moral : Jurnal kajian Pendidikan Islam, 2025)
The rapid development of technology and globalization has significantly impacted the character of younger generations, contributing to the decline of moral and spiritual values. Islamic education, especially through character-based approaches, plays a crucial role in shaping individuals with noble character. This study aims to explore the Islamic character education values contained in Kitab Al-Arba’in An-Nawawiyyah by Sheikh An-Nawawi and evaluate their relevance in the context of contemporary education. Employing a qualitative-descriptive approach with library research methods, this study analyzes 42 selected hadiths that encompass aspects of faith, ethics, and social relations. The findings reveal that divine values (e.g., piety, trust in God, and prayer) and human values (e.g., speaking kindly, helping others, and forgiveness) in this collection are highly relevant as character education solutions amid today's moral crisis. Therefore, Kitab Al-Arba’in An-Nawawiyyah is a valuable reference for integrating Islamic character education into curricula to nurture faithful, ethical, and socially responsible generations.